(untitled) (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2022)
This study is intended to see the response of moslim scholar and doctors to the article on chemical castration in The Child Protection Law in Indonesia. Muslim scholars and doctors are considered to represent the two main groups responding to that law. In this case, moslim scholar responds from the legal side, while the doctor responds from the application side. This study uses a socio-legal approach in looking at the urgency of the chemical castration and the community’s response to it. Data was collected through interviews, observation and document study. This study shows that the article on chemical castration had indeed received a rejection response from various groups, including religious scholars and doctors. This study shows that the moslim scholar basically do not reject, but just state that this type of chemical castration is not found in Islamic legal literature. However, scholars still agree with the implementation of this punishment because it can be categorized as ta’zir. As for the response from doctors, it is hoped that the executors of this punishment will not be from them, because it would be contrary to the doctor’s code of ethics, but from those usually assigned by the state for this purpose. Hence, the response from the clergy and doctors who were previously considered to be opposed could be compromised and lead to the common maslahah.